GPR124 Functions as a WNT7-Specific Co-Activator of Canonical β-Catenin Signaling - Posokhova, Ekaterina (Cell Rep, 2014)
G-protein coupled receptor 124 (GPR124) is an orphan receptor in the adhesion family of GPCRs and previous global or endothelial-specific disruption of Gpr124 in mice led to defective CNS angiogenesis and blood brain barriergenesis. Similar developmental defects were observed following dual deletion of Wnt7a/Wnt7b or deletion of β-catenin in endothelial cells, suggesting a possible relationship between GPR124 and canonical WNT signaling. Here, we show using in vitro reporter assays, mutation analysis and genetic interaction studies in vivo, that GPR124 functions as a WNT7A/WNT7B specific co-stimulator of β-catenin signaling in brain endothelium. WNT7-stimulated β-catenin signaling was dependent upon GPR124’s intracellular PDZ binding motif and a set of leucine rich repeats in its extracellular domain. This study reveals a vital role for GPR124 in potentiation of WNT7 induced canonical β-catenin signaling with important implications for understanding and manipulating CNS-specific angiogenesis and blood brain barriergenesis.